Design and Fabrication of MEMS Micro Switch for Rf Applications - Zaliman, Sauli, Prof. Madya; Hasnizah, Aris; Razaidi, Hussin; Mohd Hafiz, Ismail; Rizalafande, Che Ismail (Malaysian Invention & Design Society (MINDS), 2010)
Prof. Madya Zaliman Sauli and his team from School of Mechatronic Engineering won bronze for Design and Fabrication of MEMS Micro Switch for Rf Applications. ITEX 2006, 19th - 21st May 2006 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.